Does telling a story in reverse elicit cues to deceit? A replication and extension of Vrij, Leal, Mann and Fisher (2012) - Brimbal, Laure (Legal and criminological psychology, 2025)
Purpose The reverse order recall technique has been suggested as tool to improve deception detection accuracy. We conducted a registered replication and extension of Vrij et al., 2012's two experiments, testing whether the reverse order technique increases cues to deception in liars and accuracy in lie detection. Methods Following Vrij et al., 2012, in Experiment 1, participants were interviewed twice—once lying and once telling the truth—about a mission they completed. In both interviews, participants recounted their experience in chronological and reverse order. We coded interviews for cues to deception according to a cognitive approach: those included in Vrij et al., 2012 (replication) and others included in research on the cognitive load approach (extension). In Experiment 2, participants read two transcripts (replication) or viewed two videos (extension) from Experiment 1 and decided whether senders were lying or telling the truth in continuous (replication) and dichotomous judgements (extension). Results In Experiment 1, truth tellers were more detailed and plausible than liars. However, we failed to find the interaction between veracity and route recall reported by the original research on the replication or extensions cues. In Experiment 2, we only found an interaction between veracity and route recall for senders telling the truth on dichotomous lie detection judgement. However, this was not supported when examining overall accuracy. Conclusions These findings do not provide support for the reverse order technique as a tool to improve deception detection. We suggest further theoretical development before this technique is trained to practitioners.